2018
DOI: 10.1111/joor.12686
|View full text |Cite
|
Sign up to set email alerts
|

Association between obstructive sleep apnea and alcohol, caffeine and tobacco: A meta‐analysis

Abstract: The aim of this systematic review was to answer the focused question, "Is there an association between obstructive sleep apnea (OSA) and alcohol, caffeine or tobacco use?" Five electronic databases (Cinahl, Literatura Latth American and Caribbean, PubMed, Scopus, Web of Science) and 3 grey literature (Google Acadêmico, ProQuest, OpenGrey) were searched, as well as search on reference list of included papers and contacts with study authors. Observational studies were included. The Meta-Analysis of Statistics As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 52 publications
4
28
1
2
Order By: Relevance
“…Alcohol consumption was associated with a higher risk of sleep apnea, corresponding to the results of a meta-analysis published in 2018 [ 31 ] and those of our study. Regarding multivariate analysis, the adjusted odds ratio of subjects who quit alcoholic drinking (5.84 and P = 0.002) was higher than that of subjects who were still drinking (3.13 and P = 0.044).…”
Section: Discussionsupporting
confidence: 91%
“…Alcohol consumption was associated with a higher risk of sleep apnea, corresponding to the results of a meta-analysis published in 2018 [ 31 ] and those of our study. Regarding multivariate analysis, the adjusted odds ratio of subjects who quit alcoholic drinking (5.84 and P = 0.002) was higher than that of subjects who were still drinking (3.13 and P = 0.044).…”
Section: Discussionsupporting
confidence: 91%
“…and the glycated hemoglobin (Data not shown). Insufficient data are present regarding the relationship between coffee intake and obstructive sleep apnea [33]. The available data showed contradicting results [9,14,15] In the present study, no correlation was observed between coffee consumption and obstructive sleep apnea.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, Hsu et al 7 and Casasola et al 8 showed that smoking had no correlation with OSA. A recent meta-analysis of a total of 5264 participants in 14 studies suggested that smoking was not related to OSA, but the level of evidence in the included studies was low 9 .…”
Section: Introductionmentioning
confidence: 99%